Christian morality in Ghanaian Pentecostalism : a theological analysis of virtue theory as a framework for integrating Christian and Akan moral schemes (Regnum Books International, Oxford., 2017)
Although scholars and Christian leaders have indicated that there is marked separation between morality and spirituality in the Christian praxis of many Africans and that the African worldview, which African Christians still hold is responsible for this separation, there has not been a detailed study of the issue. The aim of the research is to offer an explanation, of a paradox in Ghanaian society where there is enthusiastic Christian spirituality that is separated from social morality, so that a deeper integration of the Christian and Akan traditional moral schemes can be proposed. My research focuses on Pentecostals in Ghana whose appropriation of the African worldview into Christian praxis has generally been considered as a positive response to African religiosity.
By the use of a practical theological method of correlation whereby the Christian truth is represented by the moral theology of John Wesley and brought in dialogue with the Akan traditional moral scheme, this research offers reasons for and proposes a solution to the lack of social morality in Ghanaian Pentecostalism. It uses the virtue theory as a heuristic tool for the analysis of morality in a way that provides explanation for the situation and guides an integration of the two moral schemes at a deeper level. The examination of the two moral schemes has been guided by the elements of character, a central theme of the virtue theory. It has been shown that the Deliverance Theology of Ghanaian Pentecostals involves significant misrepresentation of the Akan traditional scheme, and that this situation causes many Christians to focus on religion as a means for the supply of existential needs rather than the transformation of inner dispositions for moral character formation. Summary: This research shows that reinterpreting the Akan view of humanity and integrating it with the Wesleyan account of the Christian truth, transforms the Deliverance Theology by portraying the Christian life as a pneumatological characterology. The moral responsibility that this entails will ensure that African Pentecostals understand social morality as an essential outcome of their Christian spirituality.